KEBIJAKAN TAKTIS PEMERINTAH DAERAH DI PULAU JAWA DALAM PENANGANAN CORONA VIRUS DESIASE (COVID)-19 - Pramono, Joko; Siswiyanto Raharjo, Farco (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2020)
Local governments are the elements most responsible in their regions in handling Covid-19. Regional heads are required to make technical decisions which do not conflict with central government regulations. In handling Covid 19, each regional head was given the authority to carry out tactical policies. This is to suppress the spread of Covid 19 which is increasing day by day. This research method uses content analysis. Content analysis was carried out in a descriptive qualitative manner. The DKI Jakarta Government has implemented Large-Scale Social Restrictions (PSBB) to reduce the spread of Covid 19. West Java Province, establishes good communication and coordination with the central government. Then West Java has done quite well based on epidemiological indicators. So that it gets the best Covid 19 handling award in Indonesia. The Central Java provincial government in dealing with covid-19 puts forward preventive or preventive aspects. This condition can be seen from the community safari carried out by the governor of Central Java in order to provide socialization on the handling of Covid-19. East Java Province applies a cross-sectoral policy strategy. This policy involves several parties, including universities. From some of the cases above, it can be concluded that technical policy steps and fast action actions can be taken by the governments of each region on the island of Java in preventing the spread of the Covid-19 virus are correct